Structural and mechanistic insights into enantioselectivity toward near-symmetric esters of a novel carboxylesterase RoCE. Issue 24 (14th November 2022) - Dou, Zhe; Jia, Peng; Chen, Xiaoyu; Wu, Zheng; Xu, Guochao; Ni, Ye
Abstract : A novel carboxylesterase Ro CE was identified with relatively high enantioselectivity toward "hard-to-be-discriminated" oxyheterocyclic esters. Molecular basis of enantioselectivity was elucidated and applied in increasing enantioselectivity of Ro CE. Abstract : A novel carboxylesterase designated as Ro CE was identified from Rhodococcus opacus with high activity and enantioselectivity toward asymmetric esters such as ethyl 2, 2-dimethylcyclopropane-1-carboxylate (DMCPE). Moreover, Ro CE could catalyze the enantioselective resolution of near-symmetric oxyheterocyclic esters such as ethyl tetrahydro-2 H -pyran-2-carboxylate (THPCE), which are generally regarded as "hard-to-be-discriminated" by chemical and biological catalysts. The crystal structure of Ro CE was resolved at a resolution of 1.78 Å. Theozyme calculation, MD simulations and pre-reaction state analysis were performed to clarify the molecular basis for the enantioselectivity toward oxyheterocyclic carboxylic acid esters with a nearly symmetric structure. F166 plays an important role in manipulating the enantioselective recognition of ( S )- and ( R )-DMCPE through steric effect. The intrinsic symmetric structure of ( S )- and ( R )-THPCE is mainly responsible for the relatively lower enantioselectivity than DMCPE. By introducing hydrogen bond interactions, a mutant M144T was successfully obtained with an E value of 2.44-fold that of WT. MD simulations further prove the increased enantioselectivity of M144T in terms of pre-reaction state and binding free energy. This study provides a novel carboxylesterase and important molecular insights into the enantioselectivity of carboxylesterase toward heterocyclic carboxylic acid esters with a nearly symmetric structure, which will facilitate further engineering of the enantioselectivity of carboxylesterase.